A deuterium and phosphorus-31 nuclear magnetic resonance study of the interaction of melittin with dimyristoylphosphatidylcholine bilayers and the effects of contaminating phospholipase A2. - Dempsey, C; Watts, A (1987)
The interaction of bee venom melittin with dimyristolphosphatidylcholine (DMPC) selectively deuteriated in the choline head group has been studied by deuterium and phosphorus-31 nuclear magnetic resonance (NMR) spectroscopy. The action of residual phospholipase A2 in melittin samples resulted in mixtures of DMPC and its hydrolytic products that underwent reversible transitions at temperatures between 30 and 35 degrees C from extended bilayers to micellar particles which gave narrow single-line deuterium and phosphorus-31 NMR spectra. Similar transitions were observed in DMPC-myristoyllysophosphatidylcholine (lysoPC)-myristic acid mixtures containing melittin but not in melittin-free mixtures, indicating that melittin is able to stabilize extended bilayers containing DMPC and its hydrolytic products in the liquid-crystalline phase. Melittin, free of phospholipase A2 activity, and at 3-5 mol% relative to DMPC, induced reversible transitions between extended bilayers and micellar particles on passing through the liquid-crystalline to gel phase transition temperature of the lipid, effects similar to those observed in melittin-acyl chain deuterated dipalmitoylphosphatidylcholine (DPPC) mixtures [Dufourc, E. J., Smith, I. C. P., and Dufourcq, J. (1986) Biochemistry 25, 6448-6455]. LysoPC at concentrations of 20 mol% or greater relative to DMPC induced transitions between extended bilayers and micellar particles with characteristics similar to those induced by melittin. It is proposed that these melittin- and lysoPC-induced transitions share similar mechanisms.(ABSTRACT TRUNCATED AT 250 WORDS)